Reconciling Cyclical Movements in the Marginal Value of Time and the Marginal Product of Labor - Hall, Robert E. (Journal of Political Economy, 2009)
Recessions appear to be times when the marginal rate of substitution between goods and workers’ time falls below the marginal product of labor. If so, the allocation of workers’ time is inefficient. I develop a model of households and production that reconciles cyclical movements in the marginal value of time and the marginal product. The model embodies the findings of research that the Frisch elasticity of labor supply is less than one. It treats unemployment in a search‐and‐matching setup. Recessions do not result in private inefficiency in the allocation of labor, but the unemployment rate may be socially inefficiently high.